Investigating the Determinants of Financial Development in OPEC Countries: An Application of Bayesian Model Averaging Approach - Marvasti, Maryam Barzegar; Razzaghi, Somayeh (International Journal of Energy Economics and Policy, 2019)
The purpose of this study is to investigate the most significant determinants of financial development in OPEC countries during 2014-2016. To this end, this paper considered 34 explanatory variables including several economic and policy variables determining four different aspects of financial development as the degree of depth, efficiency, stability and quality of financial services. In order to obtain more reliable results and overcome the uncertainty problem in this study, we applied Bayesian Model Averaging (BMA) technique. The results indicated that better institutional indicators such as rule of law, government effectiveness, and corruption avoidance are associated with greater financial depth, efficiency, and stability. More importantly, the results revealed that the development in the oil sector could support financial development, and in particular contribute to greater depth and efficiency of the stock market. There are some important implications in this research for policymakers to promote financial development in OPEC countries. Keywords: Financial development, Oil, OPEC, Bayesian model averaging JEL Classifications: G10, G20, C11 DOI: https://doi.org/10.32479/ijeep.8498